Argumentation: A calculus for Human-Centric AI - Dietz, Emmanuelle; Kakas, Antonis; Michael, Loizos (Frontiers in Artificial Intelligence, 2022)
This paper aims to expose and analyze the potential foundational role of Argumentation for Human-Centric AI, and to present the main challenges for this foundational role to be realized in a way that will fit well with the wider requirements and challenges of Human-Centric AI. % The central idea set forward is that by endowing machines with the ability to argue with forms of machine argumentation that are cognitively compatible with those of human argumentation, we will be able to support a naturally effective, enhancing and ethical human-machine cooperation and ``social'' integration.